Risk assessment and laboratory investigation of respiratory illness in travellers returning to Singapore 2012–2015: experience from the MERS-CoV Surveillance Programme - WIN, M. K. (Epidemiol Infect, 2017)
Since the emergence of Middle East respiratory syndrome coronavirus (MERS-CoV), Singapore has enhanced its national surveillance system to detect the potential importation of this novel pathogen. Using the guidelines from the Singapore Ministry of Health, a suspect case was defined as a person with clinical signs and symptoms suggestive of pneumonia or severe respiratory infection with breathlessness, and with an epidemiological link to countries where MERS-CoV cases had been reported within the preceding 14 days. This report describes a retrospective review of 851 suspected MERS-CoV cases assessed at the adult tertiary-care hospital in Singapore between September 2012 and December 2015. In total, 262 patients (31%) were hospitalized. All had MERS-CoV infection ruled out by RT–PCR or clinical assessment. Two hundred and thirty (88%) of the hospitalized patients were also investigated for influenza virus by RT–PCR. Of these, 62 (27%) tested positive for seasonal influenza. None of the patients with positive influenza results had been vaccinated in the year prior to hospital admission. Ninety-three (36%) out of the 262 hospitalized patients had clinical and/or radiological evidence of pneumonia. This study demonstrates the potential benefits of pre-travel vaccination against influenza and pneumococcal disease.